Food Price Inflation, household characteristics, and Poverty: Empirical Evidence from South West Ethiopi: (Arsi Journal of Science and Innovation, 2025)
AbstractSustained price increases directly worsen a household's well-being by leading to greater deprivation, while underlying demographic and economic factors gradually make poverty more deeply entrenched and persistent over time. This study explores how rising food prices and household characteristics affect poverty in Ethiopia's Southwest, using data from the Household Consumption and Expenditure Survey. The research first uses the Quadratic Almost Ideal Demand System model to understand how households shift their consumption patterns in response to price change. Then, it calculates the additional money households would need to maintain their pre-price change consumption levels under three hypothetical inflation scenarios and assesses the impacts on the poverty measures. Second, the study employs a logistic regression to identify the key household characteristics that influence poverty. The findings indicate that if prices rise by 30%, households would require an additional 29% income just to keep their consumption at previous levels. This would cause the poverty rate, gap, and severity indices to increase by 17%, 6%, and 3% respectively, with food poverty measures seeing increases of 19%, 8%, and 3%. The regression analysis also reveals that poverty in the region increases with family size but decreases as income grows. These results emphasize the need for development programs to shift their focus towards rural areas, ensuring that the rural poor can also benefit from economic growth. To help the poor cope with immediate food price inflation, food aid or cash transfers could serve as effective short-term strategies. However, a more sustainable and lasting solution involves boosting food production and improving productivity by encouraging private investment in food crop sectors.